Materials used to simulate physical properties of human skin - Dąbrowska, A. K.; Rotaru, G.-M.; Derler, S.; Spano, F.; Camenzind, M.; Annaheim, S.; Stämpfli, R.; Schmid, M.; Rossi, R. M. (Skin research and technology, 2016)
Background For many applications in research, material development and testing, physical skin models are preferable to the use of human skin, because more reliable and reproducible results can be obtained. Purpose This article gives an overview of materials applied to model physical properties of human skin to encourage multidisciplinary approaches for more realistic testing and improved understanding of skin–material interactions. Methods The literature databases Web of Science, PubMed and Google Scholar were searched using the terms ‘skin model’, ‘skin phantom’, ‘skin equivalent’, ‘synthetic skin’, ‘skin substitute’, ‘artificial skin’, ‘skin replica’, and ‘skin model substrate.’ Articles addressing material developments or measurements that include the replication of skin properties or behaviour were analysed. Results It was found that the most common materials used to simulate skin are liquid suspensions, gelatinous substances, elastomers, epoxy resins, metals and textiles. Nano‐ and micro‐fillers can be incorporated in the skin models to tune their physical properties. Conclusion While numerous physical skin models have been reported, most developments are research field‐specific and based on trial‐and‐error methods. As the complexity of advanced measurement techniques increases, new interdisciplinary approaches are needed in future to achieve refined models which realistically simulate multiple properties of human skin.